Issues And Challenges In ERP Implementation : A Study On TM - Gholamzadeh Chofreh, Abdoul Mohammad (2009)
The researcher propose to conduct a case study on the issues and challenges in ERP implementation of Telekom Malaysia(TM), as well as to research about the process of ERP implementation, benefits of ERP system, Issues and challenges of ERP system and relationship between ERP and business model for this company.